Habitat and microhabitat suitability for Italian Platycerus species (Coleoptera: Lucanidae): elevation, slope aspect and deadwood features. Issue 3 (3rd April 2022) - Scaccini, Davide
ABSTRACT: Deadwood is one of the main indicators of forest biodiversity. Stag beetle (Coleoptera: Lucanidae) larvae are saproxylic organisms specialized in living in deadwood colonized by microorganisms; these beetles are bioindicators of forest integrity and are currently under threat by habitat loss, climate change and intensive forest management. A multi-year collection of data on the habitat and microhabitat deadwood-related requirements of Platycerus caraboides (Linnaeus, 1758) and Platycerus caprea (De Geer, 1774) in northern Italian forests has shed new light on the bio-ecology of these two reclusive species. They are predominantly found at medium to high elevations on north-facing slopes. Their presence – but not their abundance – is related the plant taxon, diameter and decay stage of the deadwood, predominantly belonging to the family Fagaceae but – a new finding – also to the family Salicaceae ( Salix caprea L.). Both species prefer narrow, faded, soft, very powdery, humid logs. Based on these findings, forestry management strategies should not overlook the importance of fine deadwood in managing saproxylic biodiversity in European forests.